Os efeitos de sentido das manchetes de jornais popularescos como incentivo à leitura de jornais - Santos, Gildete Cecilia Neri (2015)
In this work, we propose critical-discursive activities in mother tongue through teaching units that analyze the effects of meaning behind headlines and news in popular newspapers. We take as a source for the case study the newspaper Superpopular, from Aracaju, aired weekly from January 27, 2011 to March 27, 2014, mainly in Sergipe-Brazil. Our motivation for an educational proposal work through popular newspapers was due to the constant use of slang, jokes, proverbs and everyday phraseology, which features shocking, humorous and sensational questions in their headlines. We believe that the analysis of this corpus, from the theoretical perspective of Text Linguistics (TL) allows the accession of speeches subtly perpetuated, and collates the effects of meaning presented in these headlines and news through intertextuality, as in proverbs, songs and popular sayings consolidated in the reader's memory. These activities also allow attention to the militant and playful effect that such morphosyntatic-semantic-lexical constructions bring in order to awaken a critical-discursive reading of this genre in basic level students. Through a qualitative approach, we present, at the end of this work and in a mobile media format, pedagogical activities, especially targeting 6th to 9th junior high school graders.